Evaluating the effect of maternal factors on total and differential leucocyte count of healthy newborns in cord blood - Kumar, Ashwani; Kaur, Jaspreet (International Journal of Contemporary Pediatrics, 2016)
Background: To evaluate the effect of maternal factors (parity, age and type of delivery) on total and differential leucocyte count of healthy newborns in cord blood. Methods: The study was conducted on 200 healthy newborns admitted in neonatology section of Department of Paediatrics, Govt. Medical College/Rajindra Hospital, Patiala. Cord blood sample (2ml) was taken at birth by milking the cord into an EDTA containing vial. TLC was done by manual method (haemocytometer method) using improved Neubauer Chamber. DLC was done by Smear made from the EDTA blood stained by Leishman stain (Romanowsky group) in body and tail part of the stained smears by following Z pattern. Results: Mean TLC and DLC was done in cord blood of healthy newborns and it was compared with parity (P1, P1-P3,>P3), age of mother (<25 yrs, 25-30,>30yrs) and type of delivery (NVD/LSCS and mode of presentation. Conclusions: It was seen that maternal factors (parity, age and type of delivery) didn’t have effect on Mean TLC of newborns, whereas statistical difference for DLC in relation to maternal parity was significant for neutrophils and Monocytes and highly significant for Monocytes related to mode of presentation. However, statistical difference for Mean DLC in babies was not significant in relation to age of mother and type of delivery.